What can hide an enlarged lymph node of a patient with prostatic adenocarcinoma? - Lakić, Tanja; Šunjević, Milena; Ilić, Aleksandra; Ilić Sabo, Jelena; Radosavkić, Radosav (Vojnosanitetski pregled, 2023)
Introduction. Adenocarcinoma is the most common prostatic malignancy, where clinical management, the Gleason score, and recent updates in prostate cancer staging play critical roles. Mantle cell lymphoma (MCL) originates from the malignant transformation of B lymphocyte in the outer edge of the lymph node follicle, with pathognomonic overexpression of cyclin D1. We present a rare case of two simultaneous neoplasms occurring in the same patient. Case report. During the hospital preoperative examinations in a 68-year-old patient planned for radical prostatectomy, using multislice computed tomography, a tumor mass confined to the prostate, but also excessive lymph node enlargement, was revealed. Tissue specimens were analyzed after the hematoxylin and eosin staining was performed, as well as an immunohistochemical (IH) biomarker panel. Having performed a thorough histological examination, a diagnosis of prostatic adenocarcinoma was made, with a Gleason score 3 + 4 = 7 and Grade Group 2 of the International Society of Urological Pathology (ISUP). Microscopic analysis of lymph node involvement showed unexpected, diffuse proliferation of small lymphoid cells with irregular nuclei, wide mantle zone, and hyalinized blood vessels. After using IH staining for specific markers, another diagnosis was set, and it was non-Hodgkin MCL. Conclusion. A prostatic adenocarcinoma can rarely coexist with an undiagnosed lymphoproliferative disease, such as non-Hodgkin MCL in our case.